Trypanosomiasis in a cat- A case report - Rathod, Yashoda; Kasaralikar, Vivek R; Halmandage, Sandeep; Malasri, G (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
A sixteen-month-old female cat was presented to the department of veterinary clinical complex, veterinary college, Bidar with the history of reduced feed intake, dullness, ocular discharge from both the eyes. Clinical examination showed oedema around eyes and head, pale mucus membrane and incordination. Blood smear examination revealed the presence of Trypanosoma spp. The cat was treated with injection of isometamidium chloride along with other supportive medication and a uneventfull recovery was noticed one week post treatment.
Keywords: Cat; Trypanosomiasis; Case Report